Comparative genotyping of Streptococcus mutans by repetitive extragenic palindromic polymerase chain reaction and multilocus sequence typing - Momeni, S.S.; Whiddon, J.; Moser, S.A.; Cheon, K.; Ruby, J.D.; Childers, N.K. (Molecular oral microbiology, 2013)
Summary The genetic diversity of Streptococcus mutans has been extensively studied using a variety of genotyping methods. Repetitive extragenic palindromic‐polymerase chain reaction (rep‐PCR) is a genotyping approach used for screening large numbers of bacterial isolates. This two‐part study used multilocus sequence typing (MLST) analysis to evaluate genotypes previously identified as unique using rep‐PCR. In part one, an isolate was selected from each of the 22 S. mutans rep‐PCR genotype groups representing 8000 clinical isolates. For part two, four additional isolates were selected from the six most commonly occurring genotype groups (GG) for further analysis. Real‐time PCR was performed using eight housekeeping S. mutans gene loci and the amplicons were sequenced. Sequence data analysis was performed using CLC DNA Workbench and alleles were compared with the PubMLST database for Oral Streptococcus using the Nakano scheme. Concatenated sequences were evaluated with MEGA using a minimum evolution method with bootstrap. All 22 rep‐PCR genotypes were unique by MLST analysis. Within rep‐PCR GGs, MLST matched rep‐PCR in three groups demonstrating clonality; three groups exhibited more diversity with MLST. The discovery of three clonal groups is unique to this study and suggests that S. mutans genotypes are shared between unrelated subjects. Furthermore, MLST defined 19 new alleles and 26 new sequence types that have been confirmed and registered with PubMLST. Methods for processing were streamlined and a process for using MLST with rep‐PCR is suggested. In conclusion, MLST verified that rep‐PCR is a reliable and cost‐effective method for screening large numbers of S. mutans strains for epidemiological study.